Exploring Genetic Variability and Character Association for Morphological and Yield Traits in Sunflower (Helianthus annuus L.) - , B.V. Ravi Prakash Reddy; , B. Chandra Reddy; , Y. Prudvi Kumar Reddy; , K. Venkata Ramanamma (Archives of Current Research International, 2025)
Investigation of genetic variation and character association has huge potential for the improvement of sunflower. The present study was carried out with 75 diverse inbred lines evaluated for nine yield and their component traits. The presence of significant effects for checks vs varieties was observed for evaluated traits indicating the significant differences between varieties and checks. Based on the least significant increase value comparison over checks and ordination plots developed for seed yield per plant and oil content showed that the genotypes NDI 2, NDI 47, R 64, RHA 1096, NDLB 2, NDI 33, NDI 27 and RHA 172 were promising and could be used for the development of hybrids with high yielding and oil content in sunflower. The correlation analysis in combination with the principal component analysis revealed that the traits seed yield per plant and hundred seed weight explain most of the variation among the evaluated traits.